Implementasi Aplikasi Android Pada Antrian Pelayanan Dinas Kependudukan Dan Pencatatan Sipil (Dukcapil) Kota Palangka Raya - Sam'ani; Haris, Ferdiyani; Rosmiati; Ichsan, Mochammad; Suparno; Sulistyowati; Haris Qamaruzzaman, Muhammad (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Effective and efficient population administration services are a primary requirement in improving the quality of public services. However, the manual queuing system currently used by the Population and Civil Registration Office (Disdukcapil) of Palangka Raya City often leads to public complaints due to long queues, extended waiting times, and a lack of accessible information regarding service procedures. This community service activity aims to address these issues through the implementation of an Android-based queuing application. The program began with a needs analysis and identification of the partner's problems through field observations and interviews with staff and service users, followed by training on the use of the application for employees at the Population and Civil Registration Office of Palangka Raya. The next phase involved the development and implementation of a digital queuing application that allows citizens to take queue numbers online. The application is designed so that users can digitally obtain their queue numbers, view estimated service times, and receive real-time notifications via their mobile devices. The results of this activity indicate that the digital queuing application significantly accelerates the service process and helps reduce crowding at the service location. Based on the results of an evaluation questionnaire distributed during the community service program, the application received high satisfaction ratings, reflecting its positive impact on digital service delivery.